Manajemen Pembelajaran Keaksaraan Fungsional berbasis Duabelas Kompetensi (Survey di Kota Kendari, Kabupaten Muna, Muna Barat, Konawe, dan Konawe Kepulaun) - Rasid, Rasid; Nasir, Nasir (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
Literacy education is defined as the net generation's preparation for learning in both current and future interests, to communicate in a complex world. Therefore, learning is related to various factors, especially motivation and subject matter. Learners enter the Pathway (language deepening at various levels) at six levels starting from traditional language level, language development through exercises, language arts, advanced, up to high-level supported by education. The implementation of functional literacy programs for adults requires a new movement of reading to understand the window of the world and knowledge, individual, group, local, national and global development.